Investigating predation by the predatory bacterium Bdellovibrio bacteriovorus at the interface between predatory bacteria, pathogenic prey, and the host immune response - Clark, Callum (2023)
Bdellovibrio bacteriovorus is a Gram-negative predatory bacterium that is able to prey upon and kill other Gram-negative bacteria, including bacterial pathogens that are resistant to antibiotic treatment. This suggests that B. bacteriovorus, or components of its predatory lifecycle, may be of great use in the continued treatment of bacterial infection, as novel antimicrobial therapies. However, before B. bacteriovorus can be applied to these scenarios, we must understand how the eukaryotic immune response may alter the efficacy of predation. B. bacteriovorus has been postulated to be less immunogenic than other Gram-negative bacteria, in part due to its outer membrane containing a modified Lipid A head group that reduces detection by host pattern recognition receptors and interactions with bactericidal antimicrobial proteins, two key components of the innate immune response. However, the interactions between B. bacteriovorus and the cells of the immune system have still not been fully characterised. In the first part of my PhD, I aimed to characterise how predation by B. bacteriovorus proceeds, and may be affected, within a host. Building on previous lab findings, I discovered that, in the context of large changes in transcription, transcriptional upregulation of some major surface components by the pathogen Serratia marcescens, whilst in human serum, led to resistance to predation. The main outer membrane component implicated in this resistance period was Lipid A, which had been modified with an L-Ara(4)N sugar to reduce its negative charge. Disruption of this LPS modification pathway, through directed gene deletion, did delay the development of resistance to predation in serum, but did not abrogate it entirely, suggesting that other surface components or factors also contribute to this resistance phenotype. This work demonstrates that host environmental factors can modify Gram-negative pathogen behaviour and therefore impact the efficacy of predation by B. bacteriovorus. In the second part of my PhD, I focus on the interactions between B. bacteriovorus and macrophages, which are a key component of the mammalian innate immune system, asking what molecular factors allow B. bacteriovorus to temporarily survive for approximately 24 hours inside macrophages. This is relevant to understanding and enhancing the efficacy of predation within a human host. Focusing on genes related to oxidative stress tolerance, that are involved in prolonging the survival of pathogens within the phagosomes of macrophages, I asked whether these genes contribute to the temporary tolerance of phagosomal conditions, extending Bdellovibrio survival, and whether these genes also play a role in tolerating the oxidative stresses experienced by Bdellovibrio throughout predation. I discovered that two alkyl hydroperoxide reductase proteins and a “survival associated” chaperone protein were essential for predation, whilst a single superoxide dismutase (SodC) enzyme contributed to both predation and macrophage survival. Finally, I take a wider view on how Bdellovibrio is perceived and processed by macrophage of the host immune response asking, through investigation of the macrophage transcriptional response to engulfed Bdellovibrio. whether Bdellovibrio is recognised, phagocytosed, and destroyed in a similar way to well-characterised Gram-negative bacterial pathogens. I discovered that, although Bdellovibrio does induce a proinflammatory immune response and is subsequently killed by host macrophage after 24-48 hours, no discernible transcriptional response is initiated towards the LPS of Bdellovibrio, in stark contrast to the detection of other Gram-negative bacteria, where LPS detection forms a cornerstone of the initial immune response. This may, in part, explain the relatively low immunogenicity of Bdellovibrio seen in animal studies. This understanding can inform future applications of B. bacteriovorus as a novel antimicrobial therapy within a human host. The work presented in this thesis has further characterised the immune response to Bdellovibrio and informs us on potential considerations of, and barriers to, predation within a human host.